Contribution to the knowledge of the Protonemura corsicana species group, with a revision of the North African species of the P. talboti subgroup (Plecoptera: Nemouridae) - Vinçon, Gilles (Illiesia, 2009)
Protonemura dakkii sp. n. (Morocco) and P. algirica bejaiana ssp. n. (Tunisia)are described from both sexes and larvae. For comparison, three otherNorth African members of the Protonemura corsicana group are redescribed:P. talboti (Navás, 1929), P. algirica (Aubert, 1956) and P. berberica Vinçon & Sánchez-Ortega, 1999, and the larva of P. berberica is described for the first time. A morphological and biogeographical study of theP. corsicana group is presented. This group now comprises 31 species and 3 subspecies split in four subgroups (corsicana, talboti, consiglioi and spinulata) mainly according to the shape of the epiproct. The utility of the Protonemura tuberculata group is questioned, and a new group, Protonemura bacurianica group, is distinguished.
Keywords: entomology; Nemouridae; Plecoptera; Protonemura corsicana; new taxa; zoogeography; Oregon; larval description; taxonomy; entomologija; zoogeografija; systematics